Spin-valley locking for in-gap quantum dots in a MoS₂ transistor - Krishnan, Radha (2023)
Spins confined to atomically thin semiconductors are being actively explored as quantum information carriers. In transition metal dichalcogenides (TMDCs), the hexagonal crystal lattice gives rise to an additional valley degree of freedom with spin-valley locking and potentially enhanced spin life and coherence times. However, realizing well-separated single-particle levels and achieving transparent electrical contact to address them has remained challenging. Here, we report well-defined spin states in a few-layer MoS2 transistor, characterized with a spectral resolution of ∼50 μeV at Tel = 150 mK. Ground state magnetospectroscopy confirms a finite Berry-curvature induced coupling of spin and valley, reflected in a pronounced Zeeman anisotropy, with a large out-of-plane g-factor of g⊥ ≃ 8. A finite in-plane g-factor (g∥ ≃ 0.55-0.8) allows us to quantify spin-valley locking and estimate the spin-orbit splitting 2ΔSO ∼ 100 μeV. The demonstration of spin-valley locking is an important milestone toward realizing spin-valley quantum bits.